2006
DOI: 10.4321/s0212-71992006000800010
|View full text |Cite
|
Sign up to set email alerts
|

Consecuencias del derrame pleural

Abstract: Pleural effusion (PE) can change the equilibrium between volume of thoracic cavity and volume of intrathoracic structures, and it can disturb the function of respiratory system, heart, and diaphragm. PE alters scanty the pulmonary gas exchange, but it provokes restrictive changes in pulmonary function proportionally to fluid volume, increase thoracic diameters, and decrease lung compliance. PE can originate a syndrome similar to cardiac tamponade. Elevate intrapleural pressure increase intrapericardic pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Indeed, almost in 58% (168/293) of examinations, diaphragmatic inversion or paradoxical movement of the hemi-diaphragm was detected during inspiration, and full recovery was observed after pleural fluid evacuation. Although diaphragmatic paradoxical movement has already been reported [ 13 , 45 ], this study is the first to describe this reversible phenomenon in a considerable number of malignant effusions.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, almost in 58% (168/293) of examinations, diaphragmatic inversion or paradoxical movement of the hemi-diaphragm was detected during inspiration, and full recovery was observed after pleural fluid evacuation. Although diaphragmatic paradoxical movement has already been reported [ 13 , 45 ], this study is the first to describe this reversible phenomenon in a considerable number of malignant effusions.…”
Section: Discussionmentioning
confidence: 80%
“…Large pleural effusions can alter respiratory mechanics and lead to abnormal gas exchange, reduction in diaphragmatic function or pleural irritation. Animal models have been used to study the effects of varying pleural effusion volumes and have shown that increased pleural effusion volume is associated with decreased PaO2, increased intrapulmonary shunts and a significant decrease in left ventricular preload [ 20 22 ]. These have been verified in human patients.…”
Section: Discussionmentioning
confidence: 99%